Obstructive sleep apnea and asthma - Salles,Cristina (2013)
Symptoms of sleep-disordered breathing, especially obstructive sleep apnea syndrome (OSAS), are common in asthma patients and have been associated with asthma severity. It is known that asthma symptoms tend to be more severe at night and that asthma-related deaths are most likely to occur during the night or early morning. Nocturnal symptoms occur in 60-74% of asthma patients and are markers of inadequate control of the disease. Various pathophysiological mechanisms are related to the worsening of asthma symptoms, OSAS being one of the most important factors. In patients with asthma, OSAS should be investigated whenever there is inadequate control of symptoms of nocturnal asthma despite the treatment recommended by guidelines having been administered. There is evidence in the literature that the use of continuous positive airway pressure contributes to asthma control in asthma patients with obstructive sleep apnea and uncontrolled asthma.